اسلم انصاری کی کتاب"فیضانِ اقبال "(فکرِ اقبال کی نئی شعریات) کا اسلم توضیحی مطالعہ: An explanatory Study of Aslam Ansari’s Book “Faizan-e-Iqbal (Fikr-i-Iqbal ki Nai Sheriyat)” - عباس ڈاکٹر دبیر (Tashkeel e Jadeed, 2024)
Allama Iqbal is a poet as well as a philosopher of Urdu and Perian Language. The dissemination and universality of Iqbal’s thought and art took him out of individuality and made him a cultural heritage. His philosophical poetry has a complete system of life in it. It not only invites contemplation but also inspires action. Dr. Aslam Ansari has a special attachment to Iqbal and Iqbal’s thoughts. He is a prominent contemporary Urdu poet. Besides being a poet, he is also considered an important Iqbal Shanaas, researcher and critic. He has not only shown creative excellence in Urdu but has also written excellent poetry in Persian, English and Saraiki. His poetry comprises of many books including “Faizan-i-Iqbal”. This is the only book of poetry by Aslam Ansari which can be included in the category of poetry as well as in Iqbaliyat. In this book, on the one hand Iqbal’s thought has been created as a new poetry in the shade of Iqbal himself, on the other hand, a poetic tribute has been presented to Iqbal. In This article is an analytical study of this unique creation.